PENGARUH PEMBERIAN MIKROMINERAL (Fe, Co, Cu, Zn), VITAMIN (A, B1, B12, C) DAN JUS MENGKUDU (Morinda citrifolia L.) TERHADAP KONSUMSI PAKAN, BOBOT LEMAK ABDOMINAL DAN JUMLAH FOLIKEL OVARIUM YANG BERKEMBANG PADA PUYUH (Coturnix coturnix japonica L.) - Kurnia, Shinta Dwi; Saraswati, Tyas Rini; Isdadiyanto, Sri (BULETIN ANATOMI DAN FISIOLOGI dh SELLULA, 2015)
The purpose of the research was evaluated feed consumption, abdominal fat and amount mature folliclesfrom cultivated with combination solution of microelements (Fe, Co, Cu, Zn), vitamins (A, B1, B12, C) and morinda juice (Morinda citrifolia L.) as drinking water to optimization the productincultivation of the quail.Â Sixty quails (Coturnix coturnix japonica L.) fourteen days were divided into four treatments of combination solution microelements, vitamins and morinda juice with 15 quails in each treatments. The treatments were control, microelements and vitamins, morinda juice, and minroelements, vitamins and morinda juice. Experimental data were analyzed by using ANOVA based on completely randomized design. The result showed that combination solution of microelements, vitamins and morinda juice significant in feed consumption. Morinda juice increased feed consumption so that solution must not be used in cultivation technique of quail. Microelements and vitamins combination decreased feed consumption but not influential to mature follicles. Keywords: microelements, vitamins, morinda juice, Coturnix coturnix japonica L.